Analisis Faktor Penyebab Orientasi Seksual Menyimpang Pada Narapidana Perempuan Di Lapas Klas II A Pekanbaru - Febrya, Indrid Weddy Viva; Elmirawati, Elmirawati (Sisi Lain Realita, 2017)
The purpose of this study was to analyze: (1) the lesbian behavior description in woman’s prison, (2) deviant sexual orientation causing factors of female prisoners, and (3) appropriate treatment for lesbian behavior in women's prisons. This study was conducted in woman’s prison clas IIA, located on the Bindanak street no.1 Pekanbaru. The research was conducted in March 2018. The research using qualitative method and elaborated by descriptive analythic way. The subjects of the study were 12 female prisoners selected by purposive sampling with the following characteristics: 1. Appearance that was not gender appropriate, 2. Recognizing that having a deviant sexual orientation, 3. recommendation by the officer of prison. Data processing is done by analyzing the result of observation and interview. The result of this research is concluded that 1) lesbian description in Female prison Class IIA Pekanbaru is a female who feel herself as good man by physically and psychic. Sexual intercourse is described as two women who are attracted to each other, doing relationships like lovers. 3 people still have an interested with a man, while the other 9 people are not at all. Physical appearance of 11 subjects like as a man, the hair crop, wearing T-shirts, trousers and wear a jacket, their body language is also made dashing, While 1 person used headscarf and still seen as female, 2) The causing factors of lesbian behavior are 3 people because of environmental factor and 9 others have felt the disorder of sexual orientation since adolescence, where the abnormality is felt happened naturally and 3) treatment appropriate for lesbian in woman’s prison are to provide information services and socialization of LGBT impact on physical and psychological health, providing guidance and counseling services of individuals and groups, religious guidance and counseling services as well as religious lectures provided by experts.